By their own bootstraps: municipal commonage farmers as an emerging agrarian class in the Karoo§. Issue 3 (10th December 2018) - Atkinson, Doreen; Ingle, Mark
Abstract : Municipal commonage land in South Africa is currently utilised by resource-poor black and coloured farmers. This paper analyses information from two case studies – the Karoo towns of Carnarvon and Williston in the Northern Cape. By comparing data between 2009 and 2018, we show that a significant number of these commonage farmers have increased their livestock holdings. In addition, several have moved their livestock onto 'new' commonage farms, purchased by Government, or on land leased from white commercial farmers. We argue that the concept of 'economic class' needs to be reintroduced to South African development analysis. The paper compares these proto-commercial farmers with the 'kulak' farmers of Russia in the early twentieth century (before the Soviet regime) and the early twenty-first century (after the collapse of communism). We concur with Russian authors that the emergence of new commercial farmers may constitute a new economic class. In South Africa, the situation is of course divergent, given that a strong class of commercial farmers exists. We suggest that the commonage farming phenomenon can make a contribution to current South African land debates.